THE REPRODUCTIVE APPEARANCE OF BALINESE PIGS RAISED SEMI INTENSIVELY - Bebas, Wayan; Gorda, I Wayan (Buletin Veteriner Udayana, 2022)
This study aims to determine the reproductive appearance of balinese pigs that are raised semi-intensively. The research was conducted in Grokgak Village, Buleleng, by purposive random sampling and an exploratory approach. Data collection was carried out on several breeders using interview techniques with person/farmer group, inseminator (secondary data) and direct observations in the field (primary data). Tabulation is done on primary and secondary data and analyzed descriptively to see the mean and standard deviation. Reproductive appearance research results show : bali pigs began to experience early estrus at the age of 6.7 ± 0.78 months; initial mating 7.8 ± 0.6 months; duration of estrus 2.8 ± 0.4 days; cycle length of estrus 17.8 ± 1.40 days; signs of estrus: restlessness, refusing to eat, swollen vulva, silent when his back is pressed and the pigs respond in a ready to mate position, pigs sometimes salivate, and a distinctive voice; duration of pregnancy 111.6 ± 1.50 days; litter size 10.8 ± 0.98 tail, weaning age 2.5 ± 0.5 months; weaning weight 6.35 ± 0.79 Kg; and estrus postpartum 79.8 ± 8.02 days. It can be concluded that semi-intensive balinese pig rearing produces a fairly good reproductive performance and very promising to be maintained in dry areas because the adaptability to the environment and feed is quite good.